PROBLEMATIKA PENDIDIKAN ISLAM DI INDONESIA - Husni, Nurul; Arsy, Rahma Aulia; Fitria, Hanifah; Gusmaneli, Gusmaneli (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Islamic education in Indonesia faces a number of complex and varied problems. This article uses a qualitative research approach to gain an in-depth understanding of the problem. Through literature studies, interviews with stakeholders, and participatory observations in the Islamic education environment, this research reveals the main challenges faced, including the quality gap between formal and non-formal Islamic education, the lack of harmonization between Islamic education and the national education system, the need to increase the competence of staff educators, as well as the challenges of technology and globalization. The results of this study underscore the need for increased resources and curriculum renewal in formal Islamic education, as well as expanding access to and sustaining funding for non-formal Islamic education. In addition, there is a need for harmonization between the Islamic education curriculum and the national curriculum, so that students can develop cross-cultural skills and communicate effectively. Improving the competence of teaching staff is a priority, with more intensive training and professional development. In addition, this research highlights the importance of utilizing information and communication technology in Islamic education, as well as developing relevant strategies to maintain Islamic values and build a strong Islamic identity in the era of globalization.